Withania Somnifera: Correlation of Phytoconstituents with Hypolipidemic and Cardioprotective Activities - Uthirapathy, Subasini; Tahir, Tara F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Withania somnifera (WS) (Dunal) or Ashwagandha is a well-known hypolipidemic herb and antioxidant. In this study, 75% ethanolic extract of WS is attempted to evaluate the cardioprotective activity of isoproterenol-induced cardiotoxicity and hypolipidemic activity in Triton WR 1339-induced hyperlipidemia. In addition, phytochemical evaluation of the same extracts analyzed by gas chromatography–mass spectrometer (GC–MS). This study found that 7 days of therapy with WS extracts at 1000 mg/kg b.wt. reduced cholesterol by 76%, low-density lipoprotein (LDL) by 71%, and TAG by 12% (P < 0.05). Furthermore, it can significantly reduce cholesterol and LDL levels (P < 0.05). Similarly, the use of 50 mg/kg b.wt. of WS extract showed a cardioprotective effect against isoproterenol-induced cardiac toxic rats. The antioxidants glutathione, glutathione peroxidase, and catalase are increased in WS extract (P < 0.05), whereas the release of cardiac indicators in heart tissue is reduced (P < 0.05). Furthermore, a 30-day treatment with WS also reduced triacylglycerol in isoprenaline-induced cardiotoxic rats. GC–MS analysis of the methanol fraction of the Ashwagandha 70% ethanolic extract showed the presence of higher concentrations of fatty acids. In conclusion, WS showed hypolipidemic and cardioprotective activities in diseased animals induced by isoproterenol and Triton WR 1339.